Gaya Kepemimpinan Kepala Ruangan terhadap Kinerja Perawat - Istiqomah Istiqomah; Tuti Afriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to see the use of a computer-based expert system with the forward channeling method for detecting Gastroesophageal Reflux Disease and its application in nursing. The research method used in writing this literature review is based on 25 literature in 2018-2022. This expert system is run with PHP and MYSQL programs. The results of this study are that the Forward Chaining Expert System program will detect gastroesophageal reflux disease based on the symptoms inputted into the system and display an intervention plan that can be carried out like an expert. Still, this system cannot show 100% appropriate disease diagnosis because it requires a series of other tests that still need to be put in the system. In conclusion, with this expert system technology, health workers and users are increasingly assisted and shorten the time required for disease diagnosis and treatment. Keywords: Expert System, Forward Chaining, Gastroesophageal Reflux Disease